Gas Supply to European Union: Legal Aspects - Baghirov, Elmar (ADA University, 2013)
The paper aims at explaining the potential legal challenges Azerbaijan may face as a result of gas deliveries to the European Union. The toughening of rules on energy, especially on gas with the two regulations and three directives adopted by the Commission since 2009, has and will continue to have an enormous effect not only on member states, but also on major gas suppliers. Since the primary aim of the new energy policy of EU was to respond to the increased over-dependence from three major gas suppliers (Russia, Norway and Algeria), it is important to grasp how other states which are supposed to share and thus decrease this dependence and become a fourth core gas supplier, like Azerbaijan can be affected. Due to the fact that the Commission pays an enormous attention on the implementation of the Southern Gas Corridor Project, it is not surprising that Azerbaijan has been chosen as a case study. In addition to the risks Azerbaijan is exposed to, the measures to overcome the possible challenges that have emerged out of these new energy legislation are presented and discussed. Moreover, the projects (SCP, TANAP, TAP and NABUCCO West) and the risks all along the value chain (the Southern Gas Corridor) are assessed and demonstrated. The whole range of policies of the EU Commission to build the common energy market together with the current and possible impacts on suppliers; the present"and possible steps of suppliers to carry out above mentioned projects are evaluated and analyzed.
Keywords: Public and International Affairs; Azerbaijan -- Gas industry; Azerbaijan -- Energy Sector; European Union -- Energy sector; Internal Energy Market